ON THE NEW NATIONAL SECURITY STRATEGY OF THE RUSSIAN FEDERATION - SERGEY VLADIMIROVICH Kazantsev (Мир новой экономики)
Each state cares about its safety. The organization of action to ensure national security is legally enshrined in legislation. The Law «On security» and national security Strategy are such legislative acts in Russia at present. Already more than six years passed after «The national security Strategy of Russian Federation until 2020» became effective. Much has changed in the world and in Russia during this time much. Therefore, there isa need to adjust the strategy. The president Vladimir Putin put his finger on this point at the session of SecurityCouncil of the Russian Federation on July 2, 2015.The results of the author’s analysis of the Laws «On the safety», enacted in1992 and 2010, «The State Strategy of Economic Safety of the Russian Federation», passed in 1992, and the current «The National Security Strategy of Russian Federation until 2020». Bases himself on these documents and on the results of the study of modern threats to Russia’s security, the author proposes to have in the text of the new National Security Strategy of Russia the following subsections: 1) securable object; 2) threats, from which the object should be secured; 3) the sources of these threats; 4) the aim of the protection; 5) defenders and their responsibility; 6) forces, tools, techniques, methods of protection; 7) conditions and time of their application; 8) indicators of threats and the level of security; 9) threats and security monitoring.